2019
DOI: 10.1002/pts.2450
|View full text |Cite
|
Sign up to set email alerts
|

Shelf life extension of refrigerated breaded hake medallions packed into active edible fish gelatin films

Abstract: Fish consumption has increased in recent years. However, fish meat is highly perishable, which demonstrates the need for technologies to preserve its quality. Edible films might provide an alternative to extend the shelf life of fish. The goal of this study was to evaluate the efficiency of edible fish gelatin films added with carvacrol (blended: FG-0.6CRV and grafted: FG/CRV-g-FG) on the quality retention of commercially available prefried breaded hake medallions (BHMs). Samples of BHM were wrapped into films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…For TVB-N determinations, the distillation method of a deproteinized sample as recommended by Neira et al [25] was used. A precise amount of minced seabass muscle (5 g) was placed into a distilling flask and blended with 1.5 g of MgO.…”
Section: Total Volatile Basic Nitrogen (Tvb-n)mentioning
confidence: 99%
See 1 more Smart Citation
“…For TVB-N determinations, the distillation method of a deproteinized sample as recommended by Neira et al [25] was used. A precise amount of minced seabass muscle (5 g) was placed into a distilling flask and blended with 1.5 g of MgO.…”
Section: Total Volatile Basic Nitrogen (Tvb-n)mentioning
confidence: 99%
“…In the current research, the CK seabass samples had lower immobilized water than that of other seabass samples. Some researchers also demonstrated that water located within myofibrillar macromolecules could release or translate to free water on account of destruction of muscle fiber during storage [25,[47][48][49]. At the same time, G-βCD coatings containing eugenol retarded the change rates of T 22 and T 23 to hinder water migration, especially for G-βCD-0.15%E and G-βCD-0.3%E samples.…”
Section: Water Distribution By Lf Nmr Analysismentioning
confidence: 99%
“…However, the active packaging containing antimicrobial agents could provide a slow and continuous way for these agents migrating form packaging materials to food surfaces for a long time [12]. Carvacrol is generally recognized as safe (GRAS) defined by the US Food and Drug Administration (FDA), and has been applied to promote the shelf-life and safety of seafoods for its broad spectrum of antimicrobial and anti-biofilm activities [13,14,15]. However, the main problem limiting its application is poor solubility.…”
Section: Introductionmentioning
confidence: 99%
“…However, fish consumption is still significantly lower than in other European countries. On the other hand, people reach for the processed fish products such as ready-made fish dishes more and more often (Duman and Karaton Kuzgun, 2018; Neira et al., 2019).…”
Section: Introductionmentioning
confidence: 99%